TERAPI LATIHAN FISIK SEBAGAI TATALAKSANA CEDERA SPRAIN PERGELANGAN KAKI BERULANG: LAPORAN KASUS - Alvin Wiharja; Sri Nilawati (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2019)
Ankle sprain is a common injury that often occurs during exercise. Clinicians have been seeking various ways to deal with this injury. There are a variety of treatment options and strategies to manage this health issues in patients. However, the most effective therapy in these injuries still has not be determined.Firstable, by determining the research question: